Bringing Loyalty to E-health: Theory Validation Using Three Internet-Delivered Interventions - Crutzen, Rik; Cyr, Dianne; de Vries, Nanne K (JMIR Publications, 2011)
BackgroundInternet-delivered interventions can effectively change health risk behaviors, but the actual use of these interventions by the target group once they access the website is often very low (high attrition, low adherence). Therefore, it is relevant and necessary to focus on factors related to use of an intervention once people arrive at the intervention website. We focused on user perceptions resulting in e-loyalty (ie, intention to visit an intervention again and to recommend it to others). A background theory for e-loyalty, however, is still lacking for Internet-delivered interventions. ObjectiveThe objective of our study was to propose and validate a conceptual model regarding user perceptions and e-loyalty within the field of eHealth. MethodsWe presented at random 3 primary prevention interventions aimed at the general public and, subsequently, participants completed validated measures regarding user perceptions and e-loyalty. Time on each intervention website was assessed by means of server registrations. ResultsOf the 592 people who were invited to participate, 397 initiated the study (response rate: 67%) and 351 (48% female, mean age 43 years, varying in educational level) finished the study (retention rate: 88%). Internal consistency of all measures was high (Cronbach alpha > .87). The findings demonstrate that the user perceptions regarding effectiveness (betarange .21-.41) and enjoyment (betarange .14-.24) both had a positive effect on e-loyalty, which was mediated by active trust (betarange .27-.60). User perceptions and e-loyalty had low correlations with time on the website (rrange .04-.18). ConclusionsThe consistent pattern of findings speaks in favor of their robustness and contributes to theory validation regarding e-loyalty. The importance of a theory-driven solution to a practice-based problem (ie, low actual use) needs to be stressed in view of the importance of the Internet in terms of intervention development. Longitudinal studies are needed to investigate whether people will actually revisit intervention websites and whether this leads to changes in health risk behaviors.